The Role Of Wood-Decaying Fungi In The Carbon Cycle Of Forest Ecosystems And The Main Ecological Factors - Diyarova, Daria K. (European Scientific Journal, ESJ, 2016)
Some climatologists accept that recent climate warming is largely due to an increase in atmospheric concentrations of greenhouse gases such as carbon dioxide, methane, and nitric oxide. For this reason, studies on identification and analysis of the sources of these gases are gaining momentum. Decomposition of wood and oxidative conversion of organic carbon into CO2 carried by myco-bacterial community, in which the leading role played by fungi of the Department Basidiomycota (wood-or xylotrophic Basidiomycetes). It is organisms capable to solid-state fermentation of lignocellulosic wood complex. The role of xylotrophic basidiomycetes in biosphere currently undervalued and many aspects of ecology of these organisms are low-or not at all known. In particular, insufficiently the data about intensity of decomposition of timber, thus the conversion of organic carbon of wood into carbon dioxide pool in vivo. The external manifestation of these processes is the CO2 emissions, the activity of which is a measure of the intensity of decomposition of wood and conversion of organic carbon by fungi. The results of the study allow us to understand the role of xylotrophic basidiomycetes in the biosphere. This knowledge is needed to predict the carbon cycle of forest ecosystems under climate change and human impacts on the forest biota.